Rapid detection of Group B streptococcus directly from vaginal–rectal specimens using liquid swabs and the BD Max GBS assay. (December 2017) - Ellem, J.A.; Kovacevic, D.; Olma, T.; Chen, S.C.-A.
Abstract: Objective: We adapted the BD Max GBS assay, an automated platform for the detection of Group B streptococcus (GBS) DNA in vaginal–rectal swab specimens after LIM broth enrichment, to directly detect GBS in specimens collected using cellular foam swabs in Amies liquid medium. We compared the BD Max GBS assay performance to that of enriched culture and the BD GeneOhm StrepB assay. Methods: Seventy-two reference vaginal–rectal specimens were employed to determine the limit of GBS detection and the preferred test volume for direct detection of GBS. A total of 304 clinical specimens were then tested by the optimized BD Max GBS assay, both by direct testing and following broth enrichment. Results: The limit of GBS detection was 75 CFU/mL and the preferred test volume was 100 μL. Of 304 clinical specimens tested, GBS was detected in 62 specimens by enriched culture (20.4%); 61 of these yielded GBS by the BD Max GBS assay when performed directly from the liquid swab (sensitivity 98.4%). All 242 culture-negative specimens also yielded negative results by the BD Max GBS assay (specificity 100%). When this assay was performed following broth enrichment, GBS was detected in all 62 culture-positive specimens (100% sensitivity). The sensitivity and specificity of the BD GeneOhm StrepB assay was 90.3% and 99%, respectively. Conclusions: The BD Max GBS assay is highly sensitive, requires minimal technical skill with <2 min required to set-up, and results are available in under 80 min (versus 24–48 h for culture). It is configured for 'on demand' testing and vaginal–rectal specimens can be rapidly screened for GBS without the need for enrichment. The results obtained in this study demonstrate that rapid GBS screening using the BD Max GBS assay at the time of delivery is a viable alternative to the current recommended screening at 35–37 weeks of gestation with pre-enrichment testing methods.